2014
DOI: 10.1016/j.engstruct.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Two-way slabs: Experimental investigation of load redistributions in steel fibre reinforced concrete

Abstract: 2014): Two-way slabs: Experimental investigation of load redistributions in steel fibre reinforced concrete, Engineering Structures 80 (2014) pp. 61-74, http://dx. AbstractIn the design of two-way reinforced concrete slabs, e.g. using the strip or yield line design method, the possibility of redistributing the load between different loading directions is used. The main aim of the present study was to investigate how fibres affect the structural behaviour such as the possibility for redistribution, crack patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…However, for slabs PT32 and AM 04, the load rotation curves along both x and y directions are slightly dissimilar because of the different layout of reinforcement or column geometry in both directions. This observation was also consistent with the results from the two-way slab experiments by Fall et al [31].…”
Section: Global Structural Behaviour From Nonlinear Fe Analyses (Levesupporting
confidence: 83%
“…However, for slabs PT32 and AM 04, the load rotation curves along both x and y directions are slightly dissimilar because of the different layout of reinforcement or column geometry in both directions. This observation was also consistent with the results from the two-way slab experiments by Fall et al [31].…”
Section: Global Structural Behaviour From Nonlinear Fe Analyses (Levesupporting
confidence: 83%
“…Fall et al carried out a series of tests on two-way slabs, which have been reported in [19]; in this section only a brief description of the experiments is made. The geometry and test set-up were designed so that a flexural failure occurred.…”
Section: Experiments Of Slabsmentioning
confidence: 99%
“…Furthermore, the influence of different modelling choices on the analysis results has been investigated. The load-carrying capacity, load-deflection response, crack patterns and reaction force distribution from FE analysis of a two-way slab under a concentrated load has been compared to corresponding experimental data from Fall et al [19]. The influence of the following modelling choices has been investigated: geometrical nonlinearity, element properties, material models for concrete, reinforcement (including interaction between reinforcement and concrete), and stiffness of supports.…”
Section: Introductionmentioning
confidence: 99%
“…Only diagonal cracks propagate along the yield line, as occurred in the solid and TF-D-S-P.P slabs. In contrast, in a slab with an asymmetrical rebar arrangement, the cracks propagate perpendicular to the weak direction (Sagaseta et al 2011;Matešan et al 2012;Fall et al 2014). The legs of the merged-type fixing device increase the tensile reinforcement ratio by 0.40%, creating a strong direction and a weak direction, relative to one another.…”
Section: Crack Patternmentioning
confidence: 99%
“…Previous studies (Sagaseta et al 2011;Matešan et al 2012;Fall et al 2014) that conducted two-way bending tests used a pointed load at the center of the slab. However, with a pointed load, an unexpected punching shear failure could occur because of the concentration of shear stress around the loading point.…”
Section: Loading and Measurement Set-upmentioning
confidence: 99%